THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE AND SYSTEMATIC RISK ON EARNINGS RESPONSE COEFFICIENT WITH GOOD CORPORATE GOVERNANCE AS A MODERATION VARIABLE - Diki Ibrahim; Nofryanti; Holiawati (ZILLZELL MEDIA PRIMA, 2025)
This study examines the effect of Corporate Social Responsibility (CSR) Disclosure and Systematic Risk on the Earnings Response Coefficient (ERC), with Good Corporate Governance (GCG) as a moderating variable. Using panel data regression with the Random Effect Model (REM), the study analyzed 125 firm-year observations from energy sector companies listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. The findings reveal that CSR Disclosure has a significant positive effect on ERC, supporting the signaling theory that CSR acts as a credible indicator of firm quality and long-term sustainability. In contrast, Systematic Risk does not significantly influence ERC, suggesting that market-wide risk factors are not primary determinants of investor responsiveness to earnings announcements in the energy sector. Furthermore, GCG significantly moderates the relationship between CSR Disclosure and ERC, reinforcing the credibility of CSR disclosures and enhancing investor confidence. However, GCG does not moderate the relationship between Systematic Risk and ERC, indicating that corporate governance may not effectively mitigate the impact of external market uncertainties on earnings reactions. This study contributes to the existing literature by offering empirical insights from an emerging market context and highlighting the importance of governance and sustainability disclosures in enhancing the informativeness of earnings. The results provide valuable implications for regulators, investors, and corporate decision-makers, especially in socially sensitive and high-risk industries such as energy.